PLA2G2A+ cancer-associated fibroblasts mediate pancreatic cancer immune escape via impeding antitumor immune response of CD8+ cytotoxic T cells. (1st April 2023) - Ge, Weiyu; Yue, Ming; Lin, Ruirong; Zhou, Tianhao; Xu, Haiyan; Wang, Yu; Mao, Tiebo; Li, Shumin; Wu, Xiuqi; Zhang, Xiaofei; Wang, Yongchao; Ma, Jingyu; et al.
Abstract: Our previous research defined a novel metabolic cancer associated fibroblasts subset (meCAFs) enriched in loose-type pancreatic ductal adenocarcinoma (PDAC) and related to CD8 + T cells accumulation. Consistently, the abundance of meCAFs was associated with poor prognosis but better immunotherapy responses in PDAC patients. However, the metabolic characteristic of meCAFs and its cross-talk with CD8 + T cells remain to be elucidated. In this study, we identified PLA2G2A as a marker of meCAFs. In particular, the abundance of PLA2G2A + meCAFs was positively related to the accumulation of total CD8 + T cells and negatively correlated with clinical outcomes of PDAC patients and infiltration of intratumoral CD8 + T cells. We demonstrated that PLA2G2A + meCAFs substantially attenuated the antitumor ability of tumor infiltrating CD8 + T cells and facilitated tumor immune escape in PDAC. Mechanistically, PLA2G2A regulated the function of CD8 + T cells as a pivotal soluble mediator via MAPK/Erk and NF-κB signaling pathways. In conclusion, our study identified the unrecognized role of PLA2G2A + meCAFs in promoting tumor immune escape by impeding the antitumor immune function of CD8 + T cells, and strongly suggested PLA2G2A as a promising biomarker and therapeutic target for immunotherapy in PDAC. Highlights: PLA2G2A served as a biomarker of meCAFs by comparing the similarity between PLA2G2A + CAFs and meCAFs. The conditioned media derived from cultured PLA2G2A + meCAFs or PLA2G2A protein attenuated antitumor activity of CD8 + T cells. PLA2G2A regulated the function of CD8 + T cells via MAPK/Erk and NF-κB signaling pathways.